Natural convection heat transfer by heated partitions within enclosure - Dagtekin, I; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2001)
In this study, natural convection heat transfer and fluid flow of two heated partitions within an enclosure have been analysed numerically, The right side wall and the bottom wall of the enclosure were insulated perfectly while the left side wall and top wall were maintained at the same uniform temperature. The partitions were placed on the bottom of the enclosure and their temperatures were kept higher than the non-isolated walls. The effects of position and heights of the partitions on heat transfer and flow field have been investigated. Computations for Rayleigh number in. the range of 10(4) and 10(6) have been conducted, Using the control volume approach, finite difference equations are obtained with non-staggered grid arrangement, a computer program based on the SIMPLEM algorithm was developed. The finite difference equations were solved iteratively with a line-by-line Thomas algorithm. (C) 2001 Elsevier Science Ltd.
Keywords: Plate